Application of Complementary and Alternative Medicine Therapy on Patient with Postoperative Pain After Cardiac Surgery: a Literature Review - I Gede Nova Ariawan; Nyoman Agus Jagat Raya; Kadek Eka Swedarma (NurseLine Journal, 2022)
Pain is a devastating outcome following cardiac surgery due to routine procedures, including chest tube removal, deep breathing, and coughing exercise. Pharmacological treatment requires complementary interventions in addressing the post-acute pain phase. This study aimed to identify the application of complementary and alternative medicine (CAM) to reduce postoperative pain after cardiac surgery. A literature search was conducted by exploring original studies on the Google Scholar, PubMed NCBI, ProQuest, and ScienceDirect database that published in the last five years (2016-2021), enrolled adult participants who were undergoing cardiac surgery, and evaluated the outcome of CAM therapy on the postoperative pain after the cardiac surgery. Eighteen original studies were analyzed and synthesized. Thirteen studies employed randomized controlled trial, four studies applied quasi-experimental, and one study used one group pre-post-test design. Among these studies, ten studies focused on the manipulative and body-based practices domain (cryotherapy and massage). The application of relaxation exercise, music therapy, and distraction technique from the mind-body intervention domain was discussed in six studies. Only three studies reported the utilization of therapy from the alternative medical system, biologically-based therapy, and energy therapy domain. The majority of the CAM interventions provided significant effects in postoperative pain relief after cardiac surgery. Nurses should be able to assign appropriate CAM therapies for each patient, although all domains of CAM consider as an effective modality for postoperative pain relief after cardiac surgery. Hence, the CAM therapy would be a proper complement for the pharmacological therapies, effective in reducing the pain, and provides a chance for the patient to manage their pain independently.